Acute septic cholangitis - Estefan, Alberto; Bagnulo, Homero; Carriquiry, Luis; Cassinelli, Daniel; Pomi, Jorge; Torterolo, Edgardo; Silva, Celso (Cirugía del Uruguay, 1982)
The Panel Meeting deined Acute Septic Cholangitis as a sepsis of cholangitic orin. 60 to 90% of cases of A.S.C. are secondary to biliary lithiasis in one or other of its forms. In our media Liver Hydatid Cyst-open and evacuated on to the biliary tractand biliary cancer come after it in decreasing order of frequency. These three etiologies represent, in our casuistics, 95% of cases.